Postural assessment : an illustrated guide of 79 steps - Johnson, Jane, ....- (Champaigne : Human Kinetics, 2012)
Though postural assessment is a skill required by most therapists and useful for many health and fitness professionals, few resources offer a complete discussion of the topic to support practitioners in the task. Written for students and practitioners of massage therapy, physical therapy, osteopathy, chiropractic, sports medicine, athletic training, and fitness instruction, Postural Assessment is a guide to determining muscular or fascial imbalance and whether that imbalance contributes to a patient's or client's pain or dysfunction. Jane Johnson, a practicing physiotherapist and sport massage therapist and instructor, breaks down the complex and holistic process of assessing posture into easy-to-assimilate sections. Johnson begins with a discussion of ideal posture and the factors affecting posture as well as how to provide the correct environment for postural assessment, necessary equipment, and the importance of documenting assessment findings. Then she details procedures for executing postural assessments from standing posterior, lateral, and anterior views as well as with the patient or client in a seated position. The text features tips for improving assessment technique, and What Your Findings Mean sections provide readers—students in particular—with guidance for systematic analysis. Each chapter ends with five Quick Questions, with answers, to assist in gauging understanding of the topics covered. Information in the text is enhanced with detailed illustrations that offer visual cues to learning postural assessment and identifying anatomical relationships. Line drawings illustrate bony landmarks used in the assessments, and numerous photos show both obvious and subtle postural variations. Reproducible illustrated postural assessment charts in the appendix provide space for recording observations during each step of the assessment.